Post-acute hospital healthcare services for people with mild stroke: a scoping review. Issue 4 (19th May 2017) - Hodson, Tenelle; Gustafsson, Louise; Cornwell, Petrea; Love, Amanda
Abstract: Background : People with mild stroke comprise a significant proportion of the overall stroke population. Previously this population has been viewed as having limited impairments, receiving minimal services following hospital discharge. Recent findings demonstrate that the implications of mild stroke are more significant than originally comprehended, warranting further services. Objectives : To identify the evidence-base regarding services for people with mild stroke, post-acute hospital discharge, that target secondary prevention and/or changes following stroke. Methods : Scoping review utilizing the five-stage framework proposed by Arksey and O'Malley, with revisions by Levac, Colquhuon, and O'Brien. Framework stages included: identification of a research question and relevant studies, study selection, charting of data, and collating, summarizing, and reporting. A critical appraisal using the Downs and Black Checklist was added to determine methodological quality of studies. The search strategy used six databases: Pubmed, Embase, PsycINFO, CINAHL, OTseeker, and Scopus, alongside a hand-search. Three researchers were involved in article selection and two in critical appraisal. Results : Twelve articles met inclusion criteria from 589 identified. A number of study methodologies were used to assess services, with varying methodological qualities. Studies were located within two major regions in the world. Five main approaches to service provision were identified: telehealth, exercise and education, Comprehensive Cardiac Rehabilitation, one-off visits and care-plan development, and community group programs. The majority of programs focused on secondary prevention and were aimed at an impairment level, with a mix of findings observed. Conclusion : Further development and assessment of services is warranted. Incorporation of the entire transition period, and research that is mild stroke and location-specific is advised. Attention to maximizing participation in daily life, secondary prevention, emotional well-being, and careful reporting is needed.